Acute toxicity of Dichlorovos and Monocrotophos and their effect on respiratory metabolism of Macrobrachium malcolmsonii. - Venugopal, G; Narasimhacharyulu, V; Venkateshvaran, K (Indian Journal of Fisheries, 2011)
Acute toxicity of two organophosphorous pesticides, dichlorovos and monocrotophos were evaluated for Macrobrachium malcolmsonii. It was found that dichlorovos was more toxic than monocrotophos. M. malcolmsonii showed significant changes in the rate of respiration on exposure to lethal and sub lethal concentration. The LC50 values predict potential hazard that exist to prawn fishery particularly in polyculture grow out practices.